Prispevek k poznavanju flore osrednjih in zahodnih Karavank - Praprotnik, Nada (Hladnikia (Ljubljana), 1995)
The author discusses yhe distribution of some new and rare taxa in the Centraland Western Karavanke Mountains on both the Slovenia and Austria sides: Anemone baldensis, Astragalus australis, Dactylorhiza maculata subsp. transsilvanica, Gladiolus palustris, Hypochoeris uniflora, Lloydia serotina, Loiseleuria procumbens, Plantago atrata, saxifraga hostii, saxifraga oppositifolia, Scorzonera aristata and Sedum alpestre.
Keywords: flora; Karavanke; Karawanks; fitogeografija